Evaluasi Keselamatan dan Kesehatan Kerja dengan Metode Job Safety Analysis - Hadi Suryono; Dendy Setiady (JIEMS (Journal of Industrial Engineering and Management Systems), 2017)
PT. Laundry XYZ is a company engaged in the garment industry, especially in the field of color dye jeans. In the process of production of PT. Laundry XYZ found many potential hazards that could interfere with safety and health of workers. The potential danger caused by machines that do not operate properly and the chemicals used during the production process in PT. Laundry XYZ. Therefore, one needs to be done to eliminate the hazard control or prevent the occurrence of workplace accidents that could endanger the employees of PT. Laundry XYZ. In this study, researchers using Job Safety Analysis methods for controlling the potential hazard where data obtained from secondary data and primary data. Secondary data obtained through the company data, scientific books, and Internet media while the primary data obtained through the collection of results obtained from the questionnaire respondents employees at PT. Laundry XYZ. The method is conducted survey research that is applied, descriptive and qualitative. In this study will also be given a qualitative picture of the studied objects in the company. By performing Job Safety Analysis work on the production process in PT. Laundry XYZ is the potential danger that existed during the production process can be eliminated or controlled. The potential hazard can be controlled either by the method of technical, administrative and personal protective equipment (APD). In the process wringkled potential dangers can be controlled by modifying work tools, administration (working procedures), and provide personal protective equipment (APD) to the workers. In the washing process of the potential hazard can be controlled by modifying the working tool, the administration of the label by placing a K3 and provide protective equipment for work. In the process manequine potential dangers can be controlled by changing the way chemicals (substitution), modifying work tools, working with the administration put a label K3 and provide personal protective equipment. Results from the control of potential danger found a way or a solution to reduce the potential danger even so accidents can be prevented or eliminated. Development of Job Safety Analysis will get a new working method of an efficient and safe working on the production process at XYZ Laundry thus will improve safety and health of employees at PT. Laundry XYZ.Keywords: Keselamatan Kesehatan Kerja, Pengelolaan Limbah, Job Safety Analysis